Sustainability of Higher Education Through Distance and Online Learning during Global Educational Lockdown in Pakistan: A Case Study of Women University Multan - Munawar, Uzma; Haider, Syed Zubair; Nazeer, Husna; Hussain, Marium (Pakistan Journal of Humanities and Social Sciences, 2023)
In light of the COVID-19 Pandemic and its primary impact on day-to-day activities worldwide, numerous regulations required modification to combat this Pandemic. The lockdown began in Wuhan, China, and spread to other parts of the world, affecting the economy, education, entertainment, and government policies. This paper assesses the sustainability of higher education through distance and online learning on global educational lockdown at Women University Multan, Pakistan. A sample of 320 students from each department of Women University Multan was taken through a stratified sampling technique. A questionnaire with 18 statements was developed on Google Forms, and data was collected from the University students. The findings revealed that most students started taking online lectures using live and recorded classes. Zoom was the most frequently used platform for providing support to students, and the majority of them rated their interactions as moderate, while others rated them as excellent or good. Regarding preferences, many students preferred combining traditional learning with online learning because they were dissatisfied with their experience. The government and educational institutions need to work towards creating a sustainable education system that can adapt to changing circumstances and cater to the needs of all learners.